Proprioception in Above-the-Knee Amputees with Artificial Limbs - Latanioti, E. P. (Hindawi Publishing Corporation, 2013)
Purpose. To evaluate the lower limb proprioceptive sensation in patients with femoral amputation who received an artificial joint. Materials and Methods. 22 patients (18 men, 4 women), 24–65 years old (mean: 42), who had undergone above-the-knee joint amputation and underwent evaluation of proprioception using joint reposition in a predetermined angle of 15° knee flexion. The measurements were applied using a conventional goniometer to both amputated and healthy knees. The last ones were used as internal control. All patients performed an active knee flexion from hyperextension to 15° in a closed kinetic chain in order to evaluate proprioceptive sensation of the knee joint using the joint position sense (JPS) method during specific controllable circumstances very close to normal gait. Results. JPS at 15° flexion for the amputated knee was calculated to be equal to 13.91 (SD = ±4.74), and for the healthy side it was equal to 14.15 (SD = ±2.61). No statistically significant differences were detected between the amputated and the healthy limb (P > 0.05). Conclusions. The proprioceptive information of the stumps did not appear to be affected significantly after thigh amputation and application of artificial prosthesis when JPS at 15° was evaluated. It seems that these patients compensate the loss of the knee sensory receptors via alternative mechanisms.